Analisis Perencanaan Produksi Padi Terhadap Lahan Panen Di Sumatera Barat Menggunakan Rantai Markov Waktu Diskrit - Irfan Syauqi; Dewi Murni (UNIVERSITAS NEGERI PADANG, 2022)
Rice production is one of the results of farming which is carried out by planting rice seeds, care and maintenance and regular fertilization. While the harvest land is a plant that is harvested after the plant is old enough. Harvested land affects rice production, if the harvested area is decrease then rice production will also decrease. For this reason, it is necessary to predict rice production and harvested land in the province of West Sumatra using a discrete time Markov chain. This research aims to determine the shape of the Markov chain model and the prediction results of rice production and harvested land in the province of West Sumatra for the period January 2021 to December 2021. The results showed that the opportunities for rice production in a row were drastically decreased, decreased, increased and drastically increased by 23,28%, 17,46%, 35,46% and 23,80%. Meanwhile, the opportunities of harvesting land in a row were that drastically decreased, decreased, increased and drastically increased by 23,47%, 16,90%, 38,50% dan 21,13%.